2012
DOI: 10.1111/j.1751-0813.2011.00867.x
|View full text |Cite
|
Sign up to set email alerts
|

Haemochromatosis in a Brazilian tapir (Tapirus terrestris) in an Australian zoo

Abstract: A 23-year-old Brazilian, or lowland, tapir with a 6-month history of loss of body condition developed clinical signs and laboratory findings consistent with liver failure. The animal was euthanased and a diagnosis of hepatic haemochromatosis was made based on histopathology. Two other healthy tapirs in the same collection had chronically elevated serum and tissue iron concentrations. The excessive accumulation of iron in tissues with resultant tissue damage (i.e. haemochromatosis) has been reported in a range … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
2
4
0
Order By: Relevance
“…The liver lesions identified by microscopy were characteristic of chronic liver disease, displaying varying intensities of portal fibrosis, highlighted by Masson's trichrome, and accumulation of hemosiderin, mainly in macrophages, as evidenced by Perls stain. These injuries were identical to those described by Peters et al (2012) in Brazilian tapirs in captivity in Australia.…”
Section: Acta Amazonicasupporting
confidence: 86%
See 1 more Smart Citation
“…The liver lesions identified by microscopy were characteristic of chronic liver disease, displaying varying intensities of portal fibrosis, highlighted by Masson's trichrome, and accumulation of hemosiderin, mainly in macrophages, as evidenced by Perls stain. These injuries were identical to those described by Peters et al (2012) in Brazilian tapirs in captivity in Australia.…”
Section: Acta Amazonicasupporting
confidence: 86%
“…Based on the similarity of our histopathological and histochemical findings with those described in previous studies on tapirs (Pearson et al 1994;Bonar et al 2006;Peters et al 2012) and other animal species (Pearson and Andreasen 2001), we diagnosed the two examined tapirs with a hemochromatosis-like disease. The liver lesions identified by microscopy were characteristic of chronic liver disease, displaying varying intensities of portal fibrosis, highlighted by Masson's trichrome, and accumulation of hemosiderin, mainly in macrophages, as evidenced by Perls stain.…”
Section: Acta Amazonicasupporting
confidence: 76%
“…Studies from zoos internationally have suggested that tapirs may be susceptible to this condition. In this case report from an Australian zoo, a female Brazilian tapir had loss of body condition over approximately 6 months 5 . Following development of urinary tract signs, she became inappetant and recumbent, and was euthanased.…”
Section: Wildlife and Zoosmentioning
confidence: 90%
“…20 An estimated dosage of butorphanol (0.15-0.25 milligram per kilogram [mg/kg]) combined with xylazine (0.3-0.5 mg/kg) delivered intramuscularly (IM) produces sufficient immobilization. 59 Anesthetic induction is typically achieved by hand or remote delivery of intramuscular (free-ranging and captive) or intravenous injection (captive animal previously sedated or conditioned). 62 It is worth noting that these dosages are less than those required to achieve recumbency in domestic horses.…”
Section: Restraint and Handlingmentioning
confidence: 99%